(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article analyzes on the importance of photojournalism in documenting throught images two crucial moments in Oaxaca’s and Mexico’s recent history: the 2006 people’s movement and the incidents of June 16th, 2016, at the city of Nochixtlán. The paper reflects on some features of these historical moments, mainly about images production and their distribution, since they intervened in a distinctive way for building historicity and memory. The article also highlights how digital photography showed, at Nochixtlán, its power (through the rapidity of different media and social nets) as evidence, testimony and memory, when it intervened and impacted in the course of the incidents.